Inequitable dispersion: Mapping the distribution of highly qualified teachers in St. Louis metropolitan public elementary schools - Schultz, Lyndsie Marie (Education Policy Analysis Archives, 2014)
The No Child Left Behind (NCLB) Act of 2001 required all schools, including those located in historically disadvantaged areas, to employ highly qualified teachers. Schools in areas with higher levels of poverty and students of color have historically employed a higher percentage of less qualified teachers (Clotfelter, Ladd, & Vidgor, 2005, 2006; Hill & Lubienski, 2007; Lankford, Loeb, & Wyckoff, 2002). This study examines the distribution, location, and exceptions to highly qualified teachers in St. Louis metropolitan elementary schools. Using Geographic Information Systems (GIS), this study demonstrates how the distribution of highly qualified teachers remains relevant to urban education policy discussions.